EKONOQUIZ: TEACHERS’ ASSESSMENT AND ITS EFFECTIVENESS TO STUDENT LEARNING - Dayag, Rigin (International Journal of Sustainability and Advanced Integrated Research, 2026)
EKONOQUIZ: TEACHERS’ ASSESSMENT AND ITS EFFECTIVENESS IN STUDENT LEARNING The teaching and learning of Ekonomiks has become increasingly significant in preparing learners to understand and respond to complex economic realities in both local and global contexts. In the Philippine setting, Ekonomiks instruction faces persistent challenges such as limited instructional resources, traditional teaching approaches, and the abstract nature of economic concepts, which often result in low learner mastery, particularly in higher-order topics. These challenges highlight the need for innovative, technology-enhanced instructional and assessment strategies that can improve learner engagement and academic performance. In response to these concerns, this study aimed to determine the effectiveness of a Developed Gamified Tool in assessing and improving the academic performance of Grade 9 learners in Ekonomiks, with a specific focus on the competency “Elastisidad ng demand at supply at interaksyon ng demand at supply.” The study employed a quasi-experimental research design involving eighty (80) Grade 9 learners from selected public junior high schools in Caloocan City, divided into a control group (traditional instruction) and an experimental group (gamified instruction). In addition, seventy-two (72) Araling Panlipunan teachers from the same schools participated in evaluating the level of satisfaction and challenges encountered in using the gamified tool. Data were gathered through pretests, posttests, and researcher-made questionnaires, and were analyzed using frequency and percentage distribution, mean, and an independent samples t-test. Findings revealed that the identified Ekonomiks competency was the least mastered prior to the intervention. Results further showed that the Developed Gamified Tool was rated Very Satisfactory or Highly Acceptable across content quality, instructional quality, technical quality, and freedom from errors. Moreover, a significant improvement was observed in the posttest performance of the experimental group compared to the control group, indicating that the gamified tool was effective in enhancing learners’ academic achievement. Challenges encountered in the implementation were minimal and generally perceived as not challenging. Based on the findings, the study concludes that the Developed Gamified Tool is an effective instructional and assessment intervention in Ekonomiks, capable of improving learner engagement and academic performance while remaining highly acceptable to teachers. The results support the integration of gamified, technology-based tools in Araling Panlipunan instruction and serve as a basis for further refinement and wider implementation to address the least mastered competencies. Keywords: Academic Performance, Araling Panlipunan, Ekonomiks, Gamified Learning Tool, Grade 9, Quasi-Experimental Study.